THE ROLE OF SOCIAL MEDIA AS AN EDUCATIONAL TOOL IN INCREASING MEN'S PARTICIPATION IN VASECTOMY PROGRAMS: LITERATURE REVIEW - Puspita Sari, Dwi; Nurul Aryastuti; Sri Yunita; Damayanti (STIKes Mitra Keluarga, 2026)
Introduction : Male participation in vasectomy remains low due to limited information, stigma, and gender norms. Meanwhile, in the global era, social media provides a wide, fast, and accessible channel for delivering reproductive health education. This study reviews the role of social media as an educational tool to improve men’s understanding of and participation in vasectomy programs. Method: This literature review followed the PRISMA 2020 guidelines. Article searches were conducted in PubMed, ScienceDirect, and Google Scholar during October–November 2025 using PICO-based keywords. After a multistage selection process, eligible articles were analyzed thematically. Result: Of the 292 articles identified, eight met the inclusion criteria and were analyzed. All studies indicated that social media contributes to improving knowledge, shaping perceptions, and encouraging men’s participation in vasectomy through educational content, personal narratives, and community support, although misinformation and negative sentiment remain present on some platforms. Conclusion: Social media plays a strategic role as an educational medium to enhance men’s knowledge, positive perceptions, and participation in vasectomy. Despite persistent challenges such as stigma and misinformation, digital platforms offer substantial opportunities to strengthen reproductive health literacy and support the success of male family planning programs.